Carbon dioxide-enriched atmosphere enhances biomass accumulation and meristem production in the pioneer shrub Baccharis dracunculifolia (Asteraceae) - Mendes de Sá, Camila Emiliane; Negreiros, Daniel; Fernandes, Geraldo Wilson; Dias, Mariana Costa; Franco, Augusto César (Acta Botânica Brasílica, 2014)
The increase in atmospheric CO2 concentration predicted to the end of this century may cause several alterations on plant species development, which shall result in changes in the structure and function of plant communities. The present work aimed to investigate the effects of the increase in atmospheric CO2 concentration on the development of Baccharis dracunculifolia, a key pioneer Neotropical shrub. Seedlings of B. dracunculifolia were exposed to 720 ppm of CO2 as well as to ambient concentration of CO2 (approximately 360 ppm) during 120 days in open top chambers. Growth and dry biomass accumulation were higher under elevated CO2 concentrations. As a response to CO2 enrichment, there was an increase of 134% in total dry mass, 208% in root dry mass and 152% in stem dry mass. The shrubby habit of B. dracunculifolia and the larger number of meristems produced under high CO2 promoted the increase in 137% in the number of branches. The present study contributes to the knowledge about how pioneer tropical plants may respond to increased atmospheric [CO2] in environments with low nutrient limitation.